Use of HCV Ab+/NAT− donors in HCV naïve renal transplant recipients to expand the kidney donor pool. Issue 7 (5th June 2019) - Dao, Ann; Cuffy, Madison; Kaiser, Tiffany E.; Loethen, Ashley; Cafardi, John; Luckett, Keith; Rike, Adele Helen; Cardi, Michael; Alloway, Rita R.; Govil, Amit; Diwan, Tayyab; Sherman, Kenneth E.; et al.
Abstract: Hepatitis C (HCV) disease transmission from the use of HCV antibody‐positive and HCV nucleic acid test‐negative (HCV Ab+/NAT−) kidneys have been anecdotally reported to be absent. We prospectively analyzed kidney transplant (KT) outcomes from HCV Ab+/NAT− donors to HCV naïve recipients under T‐cell depleting early steroid withdrawal immunosuppression. Allografts from 40 HCV Ab+/NAT− donors were transplanted to 52 HCV Ab− recipients between July 2016 and February 2018. Thirty‐three (82.5%) of donors met Public Health Service (PHS) increased risk criteria. De novo HCV infection was detected at 3 months post‐KT in one recipient (1.9%). This was a case of transmission from a HCV Ab+ NAT+ donor with an initial false‐negative NAT completed using sample collected on donor hospital admission (day 2). At the time of HCV diagnosis, a stored donor sample collected during procurement (day 4) was tested and resulted NAT‐positive. Subsequently, sustained virologic response (SVR) was achieved with 12 weeks of glecaprevir/pibrentasvir. One death with functioning graft at 261 days post‐KT was determined not related to HCV or donor factors. This experience provides evidence of a low transmission rate of HCV from HCV Ab+/ NAT− kidney donors, thereby arguing for increasing utilization.